Stigma Experienced by Parkinson’s Disease Patients: A Descriptive Review of Qualitative Studies - Marina Maffoni; Anna Giardini; Antonia Pierobon; Davide Ferrazzoli; Giuseppe Frazzitta (Parkinson's Disease)
Parkinson’s disease (PD) is a neurodegenerative disease characterized by motor and nonmotor symptoms. Both of them imply a negative impact on Health-Related Quality of Life. A significant one is the stigma experienced by the parkinsonian patients and their caregivers. Moreover, stigma may affect everyday life and patient’s subjective and relational perception and it may lead to frustration and isolation. Aim of the present work is to qualitatively describe the stigma of PD patients stemming from literature review, in order to catch the subjective experience and the meaning of the stigma construct. Literature review was performed on PubMed database and Google Scholar (keywords: Parkinson Disease, qualitative, stigma, social problem, isolation, discrimination) and was restricted to qualitative data: 14 articles were identified to be suitable to the aim of the present overview. Results are divided into four core constructs: stigma arising from symptoms, stigma linked to relational and communication problems, social stigma arising from sharing perceptions, and caregiver’s stigma. The principal relations to these constructs are deeply analyzed and described subjectively through patients’ and caregiver’s point of view. The qualitative research may allow a better understanding of a subjective symptom such as stigma in parkinsonian patients from an intercultural and a social point of view.